The Pattern of Admission, Clinical Characteristics, and Outcomes Among Patients Admitted to the Intensive Care Unit of a Tertiary Hospital in Tanzania: A 5-Year Retrospective Review - Kassam, Nadeem; Adebayo, Philip; Matei, Iris; Aghan, Eric; Somji, Samina; Kadelya, Samwel; Abha, Yasson; Swai, Frank; Mabusi, Mangaro; Hameed, Kamran; Mbithe, Hanifa; Thawer, Alyyah; et al. (Patient related outcome measures, 2023)
Despite the implementation of complex interventions, ICU mortality remains high and more so in developing countries. The demand for critical care in Sub-Saharan Africa is more than ever before as the region experiences a double burden of rising rates of non-communicable diseases (NCD) in the background battle of combating infectious diseases. Limited studies in Tanzania have reported varying factors associated with markedly high rates of ICU mortality. Investigating the burden of ICU care remains crucial in providing insights into the effectiveness and challenges of critical care delivery. A single-center retrospective study that reviewed records of all medically admitted patients admitted to the ICU of the Aga Khan Hospital, Dar-es-Salaam, from 1st October 2018 to 30th April 2023. To define the population in the study, we used descriptive statistics. Patients' outcomes were categorized based on ICU survival. Binary logistic regression was run (at 95% CI and -value < 0.05) to identify the determinants for ICU mortality. Medical records of 717 patients were reviewed. The cohort was male (n=472,65.8%) and African predominant (n=471,65.7%) with a median age of 58 years (IQR 45.0-71.0). 17.9% of patients did not survive. The highest mortality was noted amongst patients with septic shock (29.3%). The lowest survival was noted amongst patients requiring three organ support (n=12,2.1%). Advanced age (OR 1.02,CI 1.00-1.04), having more than three underlying comorbidities (OR 2.50,CI 1.96-6.60), use of inotropic support (OR 3.58,CI 1.89-6.80) and mechanical ventilation (OR 9.11,CI 4.72-18.11) showed association with increased risk for mortality in ICU. The study indicated a much lower ICU mortality rate compared to similar studies conducted in other parts of Sub-Saharan Africa. Advanced age, underlying multiple comorbidities and organ support were associated with ICU mortality. Large multi-center studies are needed to highlight the true burden of critical care illness in Tanzania.